"تاثير برنامج تربية حرکيةعلي المهارات الحرکية الاساسية واثرة علي مستوي البراعة الحرکية لأطفال المرحلة الابتدائية" The effect a kinetic education program on motor skills and its impact on the level of motor dexterity of primary school children - شيماء عطية (Beni-Suef University, Faculty of Physical Education, 2022)
يهدف البحث إلى إعداد برنامج تربية حرکية ومعرفة اثرة علي مستوي البراعة الحرکية، وقد استخدم الباحثون المنهج التجريبى بتصميم المجموعة الواحدة بإستخدام القياس القبلي والبعدي على عينة قوامها (20) تلميذة ، وقد إستعان الباحثون بعينة استطلاعية والبالغ عددهم (10) تلميذات من داخل مجتمع البحث ومن خارج العينة الأساسية، وقد أسفرت النتائج إلى وجود فروق دالة إحصائيا بين متوسطي درجات القياسين (القبلي والبعدي) للمجموعة التجريبية في مستوي البراعة الحرکية (قيد البحث) لصالح القياس البعدي، مما يدل علي تحسن القياس البعدي للمجموعة التجريبية في مستوي البراعة الحرکية بدرجة دلالة معنوية، برنامج التربية الحرکية ذو تأثير إيجابي وفعال فى تنمية عناصر البراعة الحرکية لدى الأطفال من سن (6: 9). The research aims to prepare a kinetic education program and know its impact on the level of kinetic dexterity. The researchers used the experimental approach by designing one group using the tribal and remote measurements on a sample of (20) students. The researchers used an exploratory sample of (10) students from within the research community and from Outside the basic sample, the results resulted in the presence of statistically significant differences between the mean scores of the two measurements (before and after) of the experimental group in the level of motor dexterity (under research) in favor of the dimensional measurement, which indicates the improvement of the dimensional measurement of the experimental group in the level of motor dexterity with a significant degree of significance. The kinetic education program has a positive and effective effect in developing the elements of kinetic dexterity in